IJH – Immediate Job Hiring System for part-timers with location-based / Nur Suhailayani Suhaimi … [et al.] - Suhaimi, Nur Suhailayani; Halim, Faiqah Hafidzah; Arbin, Norazam; Jafar, Ainul Mardhiah (Faculty of Computer and Mathematical Sciences, 2023)
Managing temporary workers based on events and immediate hiring requires tedious, meticulous, detailed tasks. Mama Yan Selera Kampung Restaurant & Catering is a restaurant that offers food services for events to their customer located at Masjid Tanah Melaka. The restaurant was quite famous in the neighbourhood; hence it always got swamped and crowded. Due to that reason, they always hire part-timers to get the restaurant run smoothly without any problems or complaints from customers. However, a few things could be improved when hiring part-timers. It is challenging to find part-timers during an emergency, to trace and record previous data on part-timers and to gather part-timers suitable with the location of the immediate events. This project aims to develop an Immediate Job Hiring System for Part-timers with Location-Based. The objectives of this project are to gather and analyze part-timer’s data and caterer immediate events requirements, design the mobile application based on the part-timer's criteria and develop the mobile applications with location trackers. The methodology used in this project is a waterfall which includes four phases. It consists of requirement gatherings, analysis, design and implementation. A geolocation tracker was inserted to locate the registered part-timer as near as possible to the event’s venue. Thus, the part-timer finder would ease the caterer task in finding an immediate worker for their events. As for the main contribution of this project, the mobile applications are suitable for the owners to hire part-timers for the vacancies in the restaurant. The benefits include the part-timer's availability based on location, list of jobs and incoming events, and part-timer management to avoid redundancy and overlapping events for catering services.